ELECTION LAW ENFORCEMENT MODEL BY BAWASLU IN SIMULTANEOUS ELECTION IN WEST SUMATRA PROVINCE - Helmi Chandra SY; Nurbeti Nurbeti; Resma Bintani Gustaliza (STIH Putri Maharaja, 2022)
Bawaslu has one function, namely to supervise and prevent violations in elections. The existence of Bawaslu has an important meaning in avoiding the occurrence of election violations through efforts to enforce election law. This research uses sociological juridical research method, which is done by studying primary data and secondary data. The primary data referred to is obtained directly from the field by conducting interviews with informants who are related to the discussion. From the research conducted, it can be understood that the model of law enforcement by Bawaslu in simultaneous elections in West Sumatra Province is carried out through the settlement of administrative violations, the settlement of violations of the code of ethics, and the settlement of election crimes. Meanwhile, the application of the ideal model of electoral law enforcement is carried out by the method of preventing violations and taking action against violations and disputes in the election process.